REFORMULASI YURIDIS PENGATURAN PRODUK PANGAN HALAL BAGI KONSUMEN MUSLIM DI INDONESIA - Paisol Burlian (AHKAM : Jurnal Ilmu Syariah, 2014)
Juridist Reformulation of Halâl Products for Muslim Consumers in Indonesia. This paper examines the certification of halâl products that are becoming a social problem in the community as well as a responsibility of the state on the basis of the same reasoning, the assurance of halâl products. Halâl certification aims to protect the public from unlawful products and risks to health that often occur with differences of interests, especially between producers and consumers. The main source of this article is data obtained from field research that is related to the community to halâl certification LPPOM-MUI in Central and South Sumatra Province. The data is read through constructivism paradigm from a socio-legal approach with a pointed analysis of the codification theory of Islamic law, legal sociology by the American lawyer and scholar Rescoe Pound and mashlahah mursalah theory.DOI: 10.15408/ajis.v14i1.1241